Three-gluon vertex in Landau-gauge from quenched-lattice QCD in general kinematics - Pinto-Gómez F.; De Soto F. (EPJ Web of Conferences, 2022)
We report on a novel and extensive lattice QCD analysis for the three-gluon vertex from quenched lattice-QCD simulations. Using standard Wilson action, we have computed the three-gluon vertex beyond the usual kinematic restriction to the symmetric (q2 = r2 = p2) and soft-gluon (p = 0) cases where it depends on a single momentum scale. The so-dubbed bisectoral case (r2 = q2 ≠ p2), where the transversely projected vertex can be cast in terms of three independent tensors, have been the object of a recent exhaustive scrutiny [1], also shown in this communication. Herein, beyond this special case, results for kinematic configurations with three different squared momenta are also presented. All data considered, the lattice estimate of the three-gluon vertex exhibits a clear dominance of the tree-level tensor form factor.